The Legal Void in Decentralized Technologies: A Governance Model That Integrates Arbitration with AI - El-Haje Ismail, Hadil Ismail (Journal of Economic, Administrative and Legal Sciences, 2025)
Blockchain technology poses one of the most significant contemporary challenges to legal systems. Its decentralized architecture redefines traditional concepts of regulation, eliminates the role of conventional intermediaries, and relies on immutable mechanisms of record-keeping. This paradigm shift generates complex legal dilemmas, including the absence of centralized accountability, uncertainties in jurisdiction, and the opacity of regulatory structures governing autonomous digital environments. This study examines the inadequacies of traditional legal frameworks in addressing decentralized systems and proposes innovative governance models that reconcile technological innovation with the principles of legality and accountability. Employing a comparative analytical methodology, the research contrasts conventional legal doctrines with emerging technological approaches, drawing upon statutory texts, judicial precedents, and recent scholarship in law and technology. The findings reveal three central insights: (1) the legal void in decentralized systems represents a multifaceted gap at the intersection of cross-border jurisdiction, the allocation of liability, and conflicts of enforceability; (2) artificial intelligence serves as a supportive tool rather than a substitute for human decision-making, thus necessitating Human-in-the-Loop models; and (3) there is an urgent need for a normative governance framework that integrates legal regulation with mechanisms of smart code. Accordingly, the study recommends: (1) establishing a legal-technical framework for the recognition and regulation of blockchains, smart contracts, and tokens as governance instruments; (2) articulating clear standards for modern arbitration that incorporate artificial intelligence as an auxiliary mechanism, while safeguarding disclosure, independence, and professional ethics (CIArb, SVAMC); and (3) developing a phased action plan to recalibrate the trajectory of the Legal-Tech revolution in Lebanon and the Arab world through adaptive legislation aligned with technological advancements.